Deep mutational scanning of the Trypanosoma brucei developmental regulator RBP6 reveals an essential disordered region influenced by positive residues - Saúl Rojas-Sánchez; Nikolay G. Kolev; Christian Tschudi (Nature Communications)
Abstract To regain infectivity, Trypanosoma brucei, the pathogen causing Human and Animal African trypanosomiasis, undergoes a complex developmental program within the tsetse fly known as metacyclogenesis. RNA-binding protein 6 (RBP6) is a potent orchestrator of this process, however, an understanding of its functionally important domains and their mutational constraints is lacking. Here, we perform deep mutational scanning of the entire RBP6 primary structure. Expression of libraries containing all single-point variants of RBP6 in non-infectious procyclic forms and subsequent purification of infectious metacyclics supports the existence of an RNA-recognition motif (RRM) and reveal an N-terminal intrinsically disordered region (N-IDR). In contrast to the RRM, the N-IDR is more tolerant to substitutions; however, a handful of positions contain a third of all deleterious mutations found in the N-IDR. Introduction of positively charged residues in the N-IDR dramatically alters the normal metacyclogenesis pattern. Our results reveal an essential N-IDR, possibly playing a regulatory role, and an RRM likely involved in protein-RNA interactions.